Scriabin's Mature Style and the Coordination of Form, Grouping and Pitch Structures - de Médicis, François (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2009)
This article sheds new light on the tight bond that links grouping structure, form and pitch organization in Scriabin’s mature works (1907–1915). Three works are analyzed, one based on the mystic hexachord and two on the octatonic scale: the Feuillet d’album (Op. 58), Sonata No. 6 (Op. 62), and Prelude (Op. 74, No. 3). The highly frequent recurrence of material plays an important role in the coordination of the musical parameters under study—materials that are both repeated and transposed. From a pitch perspective, set properties of transpositional invariance and completion (whether octatonic or aggregate completion) play an important structural role. From a formal standpoint, these recurrences of material underpin various formal articulations and processes: the repetition of a basic idea in a presentation; the sequences in a sentence’s continuation or in a sonata transition; recurrence of a theme in the A′ of a binary or ternary form, or in the recapitulation of a sonata design. Study of the grouping structure is used as a middle-ground to help show how Scriabin coordinates pitch structure and form.